External morphological anomalies in ixodid ticks from Thrace, Turkey - GARGILI KELEŞ, AYŞEN; AKYILDIZ, GÜRKAN (SPRINGER, 2015)
Of 18,667 ticks examined, 33 specimens from species identified as Haemaphysalis parva, Hyalomma marginatum, Hy. scupense, Rhipicephalus bursa and Rh. turanicus were found to have external morphological anomalies. Anomalous Ha. parva, Hy. scupence and Rh. turanicus were reported in this study for the first time. General anomalies manifested as asymmetry and deformations of the idiosoma, whereas local anomalies occurred in legs, exoskeleton, spiracular, adanal, subanal and accessory plates, mouthparts and capitulum. With this study describing a gynandromorphic Hy. marginatum, the number of gynandromorphic tick cases has been raised to two in Turkey.
Keywords: Ticks; Anomalies; Haemaphysalis; Hyalomma; Rhipicephalus; Thrace; EMBRYONIC-DEVELOPMENT; ABNORMAL-DEVELOPMENT; RELATIVE-HUMIDITY; SENSORY ORGAN; ACARI; GYNANDROMORPHISM; ARGASIDAE; REGENERATION; TEMPERATURE; PERSULCATUS